2016
DOI: 10.4238/gmr.15038472
|View full text |Cite
|
Sign up to set email alerts
|

Molecular identification and phylogenetic analysis of important medicinal plant species in genus Paeonia based on rDNA-ITS, matK, and rbcL DNA barcode sequences

Abstract: ABSTRACT. This study was performed to identify and analyze the phylogenetic relationship among four herbaceous species of the genus Paeonia, P. lactiflora, P. japonica, P. veitchii, and P. suffruticosa, using DNA barcodes. These four species, which are commonly used in traditional medicine as Paeoniae Radix and Moutan Radicis Cortex, are pharmaceutically defined in different ways in the national pharmacopoeias in Korea, Japan, and China. To authenticate the different species used in these medicines, we evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 18 publications
(49 reference statements)
0
31
0
1
Order By: Relevance
“…Phylogenetic analysis provided a better species resolution than the nucleotide analysis (Clement and Donoghue 2012;Kim et al, 2016) and has shown that despite of the fact that all of the PeerJ reviewing PDF | (2017:11:21621:1:1:NEW 7 Feb 2018)…”
Section: Discussionmentioning
confidence: 99%
“…Phylogenetic analysis provided a better species resolution than the nucleotide analysis (Clement and Donoghue 2012;Kim et al, 2016) and has shown that despite of the fact that all of the PeerJ reviewing PDF | (2017:11:21621:1:1:NEW 7 Feb 2018)…”
Section: Discussionmentioning
confidence: 99%
“…Plant Working Group 2009). Although, the two proposed loci for barcodes are from plastid genome and includes the rbcL and matK (Techen et al, 2014), other loci including ITS1 and ITS2 are widely used for medicinal plants (Kim et al, 2016). Furthermore, the ITS2 region is suggested as a barcode for species identification over rbcL and matk (Zhang et al, 2016).…”
Section: Molecular Barcodementioning
confidence: 99%
“…The nrDNA-ITS regions were amplified using the primers ITS1 (5 -TCC GTA GGT GAA CCT GCG G-3 ) and ITS4 (5 -TCC TCC GCT TAT TGA TAT GC-3 ) with previously-reported PCR parameters [27,28]. PCR reactions were performed in 50 µL mixtures consisting of 10 mM Tris-HCl (pH 9.0), 2.5 mM MgCl 2 , 200 µM of each dNTP, 10 mM (NH 4 ) 2 SO 4 , 0.5 U Taq DNA polymerase (SolGent, Daejeon, Korea), 0.5 µM of each primer, and 15 ng of template DNA.…”
Section: Preparation Of Genomic Dna and Pcr Amplificationmentioning
confidence: 99%